Evaluating The Effects of Signal Control Applications on Roundabout’s LOS Performance Using VISSIM Microsimulation Model - M. R., Kabit; Chiew, Wai Yun; A., Chai; L. S., Tirau; Z., Bujang (International Journal of Integrated Engineering, 2023)
The existence of unbalanced and high traffic flows at roundabout have resulted in poor performance and safety concerns. Past research has shown that applications of signal control at problematic roundabouts had significantly improved its Level of Service (LOS) performance. This study investigates the effects of different signal phasing plans on the roundabout’s LOS performance using VISSIM microsimulation model. The findings revealed that both Approach-Signal-Control Roundabout ACSR and Two-Stop-Line Control Signalized Roundabout TSLSR signal phasing methods did not significantly improve the roundabout’s entry capacities. Partial signal control applications, however, have resulted in a significant reduction in vehicle delays and higher entry capacities. The results of this study provide a good overview to local traffic practitioners on how to evaluate and implement the signal control strategy at problematic roundabouts.